2008
DOI: 10.1073/pnas.0802547105
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium cellulase CelC2 is essential for primary symbiotic infection of legume host roots

Abstract: The rhizobia-legume, root-nodule symbiosis provides the most efficient source of biologically fixed ammonia fertilizer for agricultural crops. Its development involves pathways of specificity, infectivity, and effectivity resulting from expressed traits of the bacterium and host plant. A key event of the infection process required for development of this root-nodule symbiosis is a highly localized, complete erosion of the plant cell wall through which the bacterial symbiont penetrates to establish a nitrogen-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 46 publications
2
73
0
10
Order By: Relevance
“…Knockout mutants of the gene encoding the cellulase CelC2 in Rhizobium leguminosarum bv. trifolii ANU843 abolished infection thread formation (Robledo et al 2008). Ibáñez et al (2009) performed coinoculation experiments on peanut with nodule-associated species of Pseudomonas, Enterobacter, and Klebsiella together with Bradyrhizobium.…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…Knockout mutants of the gene encoding the cellulase CelC2 in Rhizobium leguminosarum bv. trifolii ANU843 abolished infection thread formation (Robledo et al 2008). Ibáñez et al (2009) performed coinoculation experiments on peanut with nodule-associated species of Pseudomonas, Enterobacter, and Klebsiella together with Bradyrhizobium.…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…Bacterial enzymes capable of degrading plant cell wall components have long been suggested to play a crucial role in establishing the nitrogen-fixing Rhizobium-legume symbiosis. Recently, Robledo et al (2008) were the first to support this hypothesis with molecular and genetic evidence by identifying a cellulase gene from R. leguminosarum. CelC2 can erode the cell wall of host root hair tips and is essential during the initial stages of symbiosis.…”
Section: Discussionmentioning
confidence: 97%
“…However, bacterial enzymes capable of breaking down plant cell wall material have long eluded identification, and induction of degradative host enzymes for remodelling the plant cell wall seemed just as likely. Only recently, Robledo et al (2008) succeeded in purifying and characterizing a cell-bound cellulase from Rhizobium leguminosarum. This CelC2 enzyme can erode the cell wall of host root hair tips and is essential for establishing a symbiosis with the R. leguminosarum host plant, white clover (Trifolium repens).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a similar phenotype as described for MOR1. Interestingly, Robledo and colleagues demonstrated that the cell-bound bacterial cellulase CelC2 is essential for the primary infection process in Rhizobium leguminosarum (Robledo et al, 2008). These data suggest that cellulytic activity is required for both proper root development and rhizobial infection.…”
Section: The Brush Phenotype Differs From That Of Previously Describementioning
confidence: 99%